Water Requirements for Large‐Scale Solar Energy Projects in the West. (August 2013) - Frisvold, George B.; Marquez, Tatiana
Abstract This study estimates how much water would be required to meet Renewable Portfolio Standards for electricity generation in five western states if 100 percent of this demand were supplied by solar power. Future renewable electricity demand (net of current supplies) is estimated for 2025 and 2035. One scenario assumes the most water‐intensive solar thermal technology supplies all this future demand. Although not a feasible scenario, the assumed water intensity (1057 gallons/MWh) provides an upper‐bound estimate of solar power water consumption that may be compared with regional water balances. A second scenario assumes the water intensity of future projects is comparable to the average of solar projects actually being deployed. Water intensity for these 34 projects with 8.7 GW of capacity averages 228 gallons/MWh – a lower rate than many conventional electricity facilities (i.e., coal, natural gas, nuclear). Water requirements by 2035 would be 0.8 percent of regional consumptive use of water under the upper bound scenario and 0.2 percent of consumptive use based on current, average water intensities.